ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KESUKSESAN PENERAPAN SISTEM INFORMASI LAYANAN PERKANTORAN (E-LAYAR): STUDI KASUS KEMENTERIAN KELAUTAN DAN PERIKANAN - Fadillah Ananda Arifah; Diny Wahyuni (Jurnal EMT KITA, 2022)
Implement an integrated system by utilizing information technology that is connected to each organizational unit or work unit was an effort to support the implementation of good governance in Ministry of Maritime Affairs and Fisheries as well as increasing administratives needs, especially in the correspondence and disposition sectors. One of the efforts is to build an application for correspondence and disposition electronically. Electronic correspondence and disposition applications or known as E-Layar (Office Services for Correspondence, Disposition, and Archives) began to be implemented in 2019 but there is some deficiency of the implementation. Based on the description, it is necessary to analyze the factors of the implementation E-Layar affect. This research uses the Updated DeLone and McLean IS Success Model success model with 6 research variables, SEM for the data analysis technique and LISREL software for the data processing. Based on the descriptive results of respondents's perceptions, all the latent variables have a good success rate. Based on the research results, all the manifest variables are valid to measure their constructs and have good reliability and based on the results of hypothesis testing with an error of 0.1 (10%), there are 4 hypotheses that are empirically proven and 5 hypothesis that are not empirically proven.